Impact of setting insecurity on Cognitive Processing Therapy implementation and outcomes in eastern Democratic Republic of the Congo. Issue 1 (31st December 2020) - Kaysen, Debra; Stappenbeck, Cynthia A.; Carroll, Haley; Fukunaga, Rena; Robinette, Katie; Dworkin, Emily R.; Murray, Sarah M.; Tol, Wietse A.; Annan, Jeannie; Bolton, Paul; Bass, Judith
ABSTRACT: Background : While evidence is growing for the efficacy of trauma-focused mental health interventions in low- and middle-income countries, concerns have been raised about whether these types of interventions can be effectively delivered in contexts with ongoing conflict and violence. Cognitive Processing Therapy (CPT) has been shown to be effective in reducing sexual violence survivors' psychological symptoms in eastern Democratic Republic of the Congo (DRC), a region with a history of chronic conflict. Objective : The purpose of the present study is to assess the degree to which exposure to different levels of ongoing insecurity impacts effectiveness of an evidence-based trauma-focused psychotherapy for sexual violence survivors. Method : Participants were 158 female sexual violence survivors receiving CPT in seven communities in South Kivu. Participants completed weekly assessments of their symptoms of PTSD and depression as part of CPT. Degree of site insecurity was categorized as high or low levels of ongoing insecurity based on information collected from supervisors and clinicians. Hierarchical linear modelling was used to examine change over time moderated by level of insecurity at the site. Results : Overall, women reported a significant reduction in psychological symptoms over time ( b = −2.04, p <.001). Residing in a site of greater insecurity was associated with higher initial symptoms ( b = 5.91, p <.01), but similar improvement over time ( b = −0.30, p =.10) compared to women living in relatively more secure sites. High rates of attendance and treatment completion were observed. Conclusions : These results support the effectiveness of trauma-focused therapies when provided in a well-structured and well-supervised program even in contexts of ongoing conflict and violence.